The Viewpoints of Sustainable Agriculture within the System Approach in Agriculture - Kroeksakul, Patarapong; Srichaiwong, Pramuk (Naresuan University Journal: Science and Technology (NUJST); Vol 23 No 1 (2015): January-April 2015, 2015)
This article has aims to present the current perception of sustainable agriculture within the systems approach. Sustainable agriculture is multi-layered and covers at component everything which correlated farm to ecology systems and livelihoods system. The sustainable evaluation within systems theory should have objectives for defining the boundaries of sustainable systems and use system properties or system behavior to explain the relation between sub-systems or components in the system. Thus, scholars should consider the function and interaction of sub-systems in order to provide an accurate analysis and reach an understanding of sustainable agriculture. Sustainable agriculture is one system with a multi-dimensional perspective, and we should therefore use the systems approach in analysis. However, the topic should take into account the philosophical principles of the individuals and organizations involved as well as relevant technology and management to discover the ways these various components interact to form the practice of sustainable agriculture. Keywords : Sustainable agriculture, systems approach in agriculture, viewpoint
Keywords: Sustainable agriculture, systems approach in agriculture, viewpoint